PENGARUH PELAKSANAAN KEBIJAKAN PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN DAN RETRIBUSI PELAYANAN PENCATATAN SIPIL TERHADAP KINERJA PENYULUHAN PENCATATAN SIPIL DALAM MEWUJUDKAN PERILAKU WARGA MASYARAKAT MENGGUNAKAN PELAYANAN PENCATATAN SIPIL DI KABUPATEN GARUT - -, Anry (Universitas Pendidikan Indonesia, 2016)
Change people's behavior in Garut is expected to be able to change for the better in terms of aware of the obligation to pay the levy, it is also determined by the role of a performance extension of the district registry office. As found in this study suggest that policy implementation Implementation of Administration of Population and Civil Registration Service Retribution effect real and positive impact on Performance and Behavior Counseling Civil Registration Citizens using the Civil Registry Service. The implications of the findings in this study are the phenomenon of obstruction of efforts to deliver information program of birth certificates to the public, resulting in low levels of participation and public confidence in the civil registration services. This condition will affect the low orderly population administration in the community.